The Development of “I-GEP” (Infographic of Elements and Principles of Design) module as scaffolding in teaching and learning visual arts for secondary school / Fauziah Mohammad - Mohammad, Fauziah (2019)
Infographic or “information graphic” are designed and used in the current study as instructional material to scaffold in teaching and learning process. This study examined the use of “I-GEP” (Infographic of Elements and Principles of Design) Module that has been design and developed as a teaching tool for facilitating teaching and learning Visual Arts Education. This study was conducted and focussing in Elements and Principles of Design topic in VAE among Form Four secondary school students and Visual Art teacher. This study also assesses students’ achievement in summative test, artwork produced, and their feedback on gallery walk activities conducted. Besides, the usability of the module had been evaluate after lesson completed. This study was used Design Developmental Research (DDR) as research design which is consist three phase in developmental study. The I-GEP module was developed using ADDIE model supported by Learning and Remembering Equation Instructional Design Model by Sharon Boller (2017) as a guide in developing Visual Art lesson plan and to be used in teaching and learning process. The data collection is based on methodology using quantitative and descriptive statistics. The data finding from qualitative method is supported in this study. This study conducted with 176 students and five experts in phase one for Need Analysis. For Design and Development in phase two was evaluated by four experienced teacher of VAE. In the phase three for implementation and evaluation procedure, research conducted through quasi-experimental of single-group comparison study. The respondent in this phase were selected through purposive sampling of 43 students which consist 30 male and 14 female and one Visual Art teacher. This result revealed significantly higher achievement on mean total score of students’ summative test after using I-GEP Module. This shows that the use of I-GEP module has succeeded in improving student achievement in learning. The usability test also revealed 100% teacher were satisfied with the productivity of the module and students for both gender shows same interest in learning I-GEP module through interactive while female students shows higher interest in learning I-GEP through printed material than male students. Conclusion are drawn, and directions for future studies are discussed.